TINGKAT KEPATUHAN WAJIB PAJAK ORANG PRIBADI DALAM MELAPORKAN e-SPT PAJAK PENGHASILAN PADA KANTOR PAJAK (KPP) PRATAMA MAKASSAR BARAT - Abdul Wahab (Jurnal Riset Perpajakan: Amnesty, 2020)
This study aims to determine the level of individual taxpayer compliance in reporting e-SPT income tax at the Pratama West Makassar Tax Office (KPP). The type of research used is descriptive and qualitative where the researcher describes the results of the observations and analyzes the data based on what is obtained in the field. The research was conducted from 1st  May to 31 June 2020. And after conducting analysis and discussion at the West Makassar tax service office (KPP), the researchers concluded that the level of taxpayer compliance at the West Makassar Tax Office (KPP) Pratama West Makassar shows that individual taxpayers in reporting e-SPT Taxes in a timely manner are classified as lacking. obey this because the percentage level of compliance from 2018 to 2019 has decreased from year to year. Due to several factors, namely the taxpayer does not know the due date for reporting the e-SPT for Income Tax, the taxpayer forgets to report t he e-SPT and also the taxpayer is not in Makassar City so that the taxpayer cannot report the e-SPT.Abstract written in English which contains the main issues, research objectives, methods / approaches and research results. Abstract written in one alenia, no more than 250 words.